Experimental evolution of the grain of metabolic specialization in yeast. Issue 12 (11th May 2016) - Samani, Pedram; Bell, Graham
Abstract: Adaptation to any given environment may be accompanied by a cost in terms of reduced growth in the ancestral or some alternative environment. Ecologists explain the cost of adaptation through the concept of a trade‐off, by which gaining a new trait involves losing another trait. Two mechanisms have been invoked to explain the evolution of trade‐offs in ecological systems, mutational degradation, and functional interference. Mutational degradation occurs when a gene coding a specific trait is not under selection in the resident environment; therefore, it may be degraded through the accumulation of mutations that are neutral in the resident environment but deleterious in an alternative environment. Functional interference evolves if the gene or a set of genes have antagonistic effects in two or more ecologically different traits. Both mechanisms pertain to a situation where the selection and the alternative environments are ecologically different. To test this hypothesis, we conducted an experiment in which 12 experimental populations of wild yeast were each grown in a minimal medium supplemented with a single substrate. We chose 12 different carbon substrates that were metabolized through similar and different pathways in order to represent a wide range of ecological conditions. We found no evidence for trade‐offs between substrates on the same pathway. The indirect response of substrates on other pathways, however, was consistently negative, with little correlation between the direct and indirect responses. We conclude that the grain of specialization in this case is the metabolic pathway and that specialization appears to evolve through mutational degradation. Abstract : This work provides insight into the process of metabolic specialization in experimental populations of wild yeast. We selected yeast populations in 12 single‐substrate selection regimes. We evaluated the direct and indirect response to selection and concluded that the grain of specialization in this case (our experiment) is the metabolic pathway rather than individual substrates and that specialization appears to evolve through mutational degradation.